Persepsi Siswa Terhadap Pembelajaran Kolaboratif Dalam Kelas Menulis Di Sekolah Menengah Kejuruan - Akbar, Khoidir Ali; Srisudarso, Mansyur; Wahyuna, Yuna Tresna (Peneliti.net, 2024)
Khoidir Ali Akbar, Student’s Perception In Collaborative Learning On Writing Class For Vocational High School. Department of English Education. Faculty of Teacher Training and Education. University of Singaperbangsa Karawang. 2023. In the context of education at the high school level, the significance of effective writing skills cannot be understated. This qualitative study examines the perceptions of students from the mechanical engineering major at State Vocational High School 1 Karawang regarding collaborative learning in their writing class. The research, conducted through interviews with five respondents, aimed to explore the impact of collaborative writing on their engagement, writing skills, and exposure to diverse viewpoints. The findings indicate a positive influence of collaborative writing, enhancing students' writing abilities and facilitating exposure to a range of perspectives. However, the study also identifies challenges related to scheduling coordination and managing the variety of opinions within groups. Through an inclusive discussion of academic perspectives, this study highlights the various nature of collaborative writing as a potent tool for learning. In conclusion, collaborative writing in English class offers students an approach to improve their writing skills, develop their understanding of different perspectives, and valuable teamwork abilities. By addressing challenges and increasing the role of teachers in guiding students, collaborative writing can become an essential component of a comprehensive and improving educational experience.